Implementasi Manajemen Mutu Terpadu untuk Meningkatkan Kompetensi Lulusan Sekolah Menengah Atas - Mutaqin, Imam; Zaki, Muhammad (Dir?s?t: Jurnal Manajemen dan Pendidikan Islam, 2018)
This research aimed at investigating the impact of integrated quality management on education quality at SMA DU 2 BPPT Jombang. To get the result, this research was qualitative and applied field research method. Non-participant method was used to get data for six months. It was also aided supported data and by the result of interview with all participant. Furthermore, validation data used triangulation method. Next the data was observed and interpreted. The result revealed that SMA DU 2 BPPT implemented integrated quality management in term of human resource, curriculum and education facility. It is therefore impact on the increasing of quality which is proved by their70 % alumnae study in grade A state university for three last year. Then, it also increases the satisfaction of the student and also their parent as the customer.